Thermal analysis of rubbers and rubbery materials - Choudhury, Namita Roy; De, Prajna P.; Dutta, Naba K. (ISmithers, 2010)
Thermal analysis is a group of techniques in which a physical property of a substance is measured as a function of temperature, while the substance is subjected to a controlled temperature programme. In differential thermal analysis, the temperature difference that develops between a sample and an inert reference material is measured, when both are subjected to identical heat treatments. The related technique of differential scanning calorimetry relies on differences in energy required to maintain the sample and reference at an identical temperature.